Readiness to change among e-hailing drivers in Klang Valley / Cherry Ashley, Nur Athirah Mohamadzin and Nurul Syahirah Hussin - Ashley, Cherry; Mohamadzin, Nur Athirah; Hussin, Nurul Syahirah (2020)
The study was carried out on MeHDA with regards to the readiness of change among e-hailing drivers in Klang Valley. The role of MeHDA is to help, support, and protect the e-hailing drivers’ rights. This is especially needed when the government has decided to enforce the conditions for e-hailing drivers at the same level as taxi drivers in which the e-hailing drivers do not have the readiness to change. This is because too much cost needs to be borne, especially for part-time e-hailing drivers. In 2019, there was a shortage of e-hailing drivers around 20% to 50% due to the newly imposed government rules and regulations. This research aimed at studying on the readiness to change among e-hailing drivers in Klang Valley. It specifically focused on e-hailing drivers around Klang Valley area. This study adopted a descriptive analysis as its research method and convenience sampling as its sampling technique. This research was based on data obtained from a survey that inquired e-hailing drivers’ responses regarding their readiness to change. The data were then analysed to examine the relationship of readiness to change among e-hailing drivers in Klang Valley. The findings of this study showed that as independent variables (IV), process of change and work engagement were significantly influenced by the dependent variable (DV), i.e., readiness to change. Meanwhile, trust in management and organisational commitment as IV was not significantly influenced by the DV, i.e., readiness to change. Therefore, the findings revealed that process of change is the most prominent factor that impacts readiness to change among e-hailing drivers as its beta value was the highest compared to other independent variables.